2017
DOI: 10.1186/s12967-017-1275-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of IQGAP3 in metastasis and epithelial–mesenchymal transition in human hepatocellular carcinoma

Abstract: BackgroundHepatocellular carcinoma (HCC) is one of the most lethal cancers worldwide owing to its high rates of metastasis and recurrence. The oncogene IQ motif-containing GTPase activating protein 3 (IQGAP3) is ubiquitously overexpressed in several human cancers, including liver, ovary, lung, large intestine, gastric, bone marrow, and breast malignancies and is involved in the invasion and metastasis of cancer cells. Therefore, we aimed to determine the biological role and molecular mechanism of IQGAP3 in HCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 42 publications
1
53
0
Order By: Relevance
“…Recently, IQGAP3 expression was found to be related to clinical stage and was an independent prognostic classifier of gastric cancer patients: IQGAP3 knockdown reduced both the number and size of the spheres formed by the gastric cancer cell line MKN-74 and inhibited the phosphorylation of Akt and Erk1/2[11]. In hepatocellular carcinoma, IQGAP3 was reported to function as an important regulator of epithelial-mesenchymal transition (EMT) and metastasis by activating the transforming growth factor (TGF)-β signaling pathway[9]. Regarding breast cancer, IQGAP3 knockdown by RNA interference inhibited cell proliferation and invasion in two breast carcinoma cell-lines[12].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, IQGAP3 expression was found to be related to clinical stage and was an independent prognostic classifier of gastric cancer patients: IQGAP3 knockdown reduced both the number and size of the spheres formed by the gastric cancer cell line MKN-74 and inhibited the phosphorylation of Akt and Erk1/2[11]. In hepatocellular carcinoma, IQGAP3 was reported to function as an important regulator of epithelial-mesenchymal transition (EMT) and metastasis by activating the transforming growth factor (TGF)-β signaling pathway[9]. Regarding breast cancer, IQGAP3 knockdown by RNA interference inhibited cell proliferation and invasion in two breast carcinoma cell-lines[12].…”
Section: Introductionmentioning
confidence: 99%
“…IQGAP3 has also been associated with markers of apoptosis and metastasis. Shi and colleagues have shown that epithelial-mesenchymal transition (EMT) markers including e-cadherin, fibronectin, vimentin, n-cadherin are overexpressed in HCC cells with up-regulation of IQGAP3, while knockdown of IQGAP3 showed the reduction of the above markers [45]. Furthermore, IQGAP3 functions as an important regulator of metastasis and EMT by constitutively activating the TGF-beta signaling pathway; hence, it may also play some roles in promoting cancer stemness through regulation of tumor microenvironment [46].…”
Section: Discussionmentioning
confidence: 99%
“…PTTG1 has been reported to be associated with poor prognosis and angiogenesis in HCC (35). IQGAP3 functions as a potential oncogene by activating metastasis and EMT in HCC (36). CDKN3 has been correlated with poor tumor differentiation and advanced tumor stage by promoting cell proliferation in HCC (37).…”
Section: Discussionmentioning
confidence: 99%